Peran Pemerintah Kabupaten Bulungan Dalam Peningkatan Kualitas Hasil Panen Pisang di Desa Sajau Hilir Sebagai Upaya Meningkatkan Kesejahteraan Masyarakat - Al Bahasyim, Muhammad; Soimah, Nurus; Imelda, Dewi Qomariah; A, Aslan; H, Hermawan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study was to determine the role of the Bulungan district government in improving the quality of banana crops in the village of Downstream as an effort to prosper the local community. The type of research used descriptive research with a qualitative approach. Data collection techniques used were observation, interview and documentation. The respondents in this study were local people, both farmers and village officials. The results of the study showed that the role of the Bulungan district government in increasing the quality of banana harvest in the village of Sajau Hilir is going well; Field extension workers have already been carried out such as providing fertilizer and conducting the training for banana farmers until the post-harvest processing stage, but the problem faced by farmers were that the selling price of bananas has decreased sharply so that many have left, at this time the government was more focused on increased production of rice, soybeans, and corn, this is one of the causes of banana plantations being used by the farmers in the lower reaches of the village.